A Comparision of Blood Glucose Level Measured by Standard Laboratory Procedure with That of Five Glucometer Devices in Patients with Diabetes Mellitus - Mansoor EbrahimZadeh (Golestan University of Medical Sciences, 2013)
Background and objective: Diabetes Mellitus (DM) leading to increasing risk in the health of society is one of the main problems worldwide. ‌The main goal is having normal blood glucose to reduce the progression of neurovascular complications. We aimed at comparing the performance of five glucometer devices with that of standard laboratory technique in patients with DM admitted to endocrinology ward of Razi Hospital in Rasht. Material and Methods: ‌This comparative-analytic study was conducted on 250 diabetic patients. A part of venous blood sample ‌was investigated by‌ five glucometer devices (Glucoplas‌, Accu-chek‌, Easyguloco‌, Bionime and On-kalyz) and the remaining tested by standard laboratory technique. The data was analyzed by SPSS software, using paired-‌t‌-test. Results: The results showed that the mean of Glucoplus was the least (237.52) and that of On-kalyz was the highest (297.82). Using Paired-sample t-test, the mean difference between venous blood glucose by Glucometer and that of standard laboratory technique was reported in order 2.40 mg/dl for Bionim, -3.62 mg/dl for Easyguloco and -4.34 for Accu-chek Glucometer. Glucoplas and Onkalyz were significantly different from Laboratory standard method (p<0.0001). Conclusion: The mean difference of On-kalyz and Glucoplas glucometer devices that is orderly greater than the mean difference of laboratory standard method are less reliable for measuring blood glucose levels, compared to Bionime‌, Easyguloco avd Accu-chek having the least difference.